Time-temperature shift factor determination of woven epoxy laminate using dynamic mechanical analyzer (DMA) - Lim, Babara Fong Chin. (2013)
An accelerated testing methodology using Time-Temperature Superposition Principle was employed in this study on one ply and two ply woven Carbon Fiber Reinforced Polymer specimens. This concept overcomes the difficulty of extrapolating limited laboratory tests at shorter times to longer-term behaviour. This temperature and frequency dependency of polymers were demonstrated in the master curves of storage moduli and horizontal shift factors for both specimens. It was concluded that the effect of frequency scan resulted in an earlier transition and it registered a greater deterioration of the storage modulus than the experiment which was conducted with temperature scan at a fixed frequency.